Comparison of immunofluorescence and hemagglutination inhibition tests and enzyme-linked immunosorbent assay for detection of serum antibody in rats infected with hemorrhagic fever with renal syndrome virus. - Takahashi, Y (1986)
Serum antibodies against the B-1 strain of hemorrhagic fever with renal syndrome (HFRS) virus in wild and experimental rats were investigated by the indirect immunofluorescent antibody (IF) test, the hemagglutination inhibition (HI) test, and an enzyme-linked immunosorbent assay (ELISA). In the newly developed ELISA, monoclonal antibodies to the B-1 strain were applied as coating antibody. In sera from wild rats, the results obtained by the ELISA agreed quite well with those obtained by the HI test, but some serum samples that gave a negative reaction in the HI test gave a positive reaction in the IF test, although their IF titers were very low. In serum samples from experimental rats that had been kept in an animal house infected with HFRS virus, a group with high titers and a group with low or negative titers were clearly differentiated by all the tests.